(Un)Seeing Augustus: Libertas, Divinisation, and the Iuvenis of Virgil's First Eclogue. (November 2021) - Xinyue, Bobby
Abstract: This article argues that Virgil's First Eclogue naturalises the power discourse of the future Augustan Principate. Throughout the poem, Virgil not only presents the iuvenis as a libertas -restoring benefactor who is treated as a god by his beneficiaries, but even imagines his elevated status as crucial to maintaining social cohesion and civic stability, and idealises the beneficiaries' dependence on his efficacious authority. The poem thus produces the grammar of the discourse of authoritarianism, subtly articulating what will eventually become the central tenets of Augustan ideology. I suggest that it is precisely this process of naturalisation which has led readers since antiquity to identify the iuvenis of Virgil's First Eclogue as the future Augustus. However, in this paper I am interested in transcending this question of individual identification to focus instead on how Virgil's poetic anonymisation is no simple pastoral obfuscation, but rather does the hard graft of 'soft launching' a new political system.